DIRECTIONS FOR IMPROVING FINANCIAL STATEMENTS OF ELECTRICITY NETWORK ENTERPRISES BASED ON IFRS (World Economics and Finance Bulletin, 2025)
The article develops directions for improving the financial statements of electricity grid enterprises based on International Financial Reporting Standards (IFRS).
Keywords: IFRS; ECL model; financial statements; electricity losses